Analisis Faktor – Faktor yang Mempengaruhi Underpricing pada Saat Initial Public Offering: Studi Pada Perusahaan Go Public di BEI Tahun 2017-2020” - Endah Purnama Sari; Fida Muthia; Shelfi Malinda; Muizzudin Muizzudin; Isni Andriana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study intends to examine the factors that influence the amount of underpricing of equities during initial public offerings on the Indonesia Stock Exchange. This analysis makes use of secondary data in the form of financial statement data and other firm information from 2017-2020 IPOs on the Indonesia Stock Exchange. The research sample consisted of 150 firms selected using techniques of purposive selection. This study employs the linear regression approach of panel data using STATA for its data analysis. The results indicated that the company's age, size, and financial leverage had no influence on the underpricing of its shares. The reputation of underwriters and profits per share have a substantial negative impact on the stock's underpricing. The elements that effect stock underpricing, particularly underwriter reputation and earnings per share, may be employed by investors who will invest in a business in order to generate profits, and by firms that will make an initial public offering (IPO) in order to improve their situation.